SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170966-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Model for Wettability Alteration by Chemically Tuned Water Flooding in Carbonate Reservoirs

Abstract: Injection of chemically tuned brines into carbonate reservoirs has been reported to enhance oil recovery by 5% to 30% OOIP in core flooding experiments and field tests. One proposed mechanism for this improved oil recovery (IOR) is wettability alteration of rock from oil wet or mixed-wet to more water wet conditions. Modeling of wettability alteration experiments, however, are challenging due to the complex interactions among ions in the brine and crude oil on the solid surface. In this research, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…Thereafter, the rock no longer dissolves (or precipitates) and can no longer etch to release oil. The fact that carbonates equilibrate rapidly with brine necessitates a detailed understanding of aqueous-speciation chemistry (Al-Shalabi et al 2014;Alotaibi and Yousef 2015;Qiao et al 2014Qiao et al , 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the rock no longer dissolves (or precipitates) and can no longer etch to release oil. The fact that carbonates equilibrate rapidly with brine necessitates a detailed understanding of aqueous-speciation chemistry (Al-Shalabi et al 2014;Alotaibi and Yousef 2015;Qiao et al 2014Qiao et al , 2016.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we demonstrate that injected brine almost immediately equilibrates with carbonate rock. Thus, the assessment of aqueous speciation chemistry is paramount to LSW (Al-Shalabi et al 2014;Qiao et al 2014Qiao et al , 2016. Also pertinent to LSW in carbonates are high-salinity brine and lack of clay content, both of which affect the DLE recovery mechanism.…”
mentioning
confidence: 99%
“…The f-potential measurements were conducted with the f-potential analyzer (Zetapals).The Zetapals instrument uses a phase-analysis light-scattering technique to determine the electrophoretic mobility (measure of speed) of charged colloidal suspensions, and calculates the f-potential (in mV) with the Smoluchowsky and Huckel models (Sze et al 2003). One can write Smoluchowsky's equation as follows:…”
Section: Zeta (F) -Potentialmentioning
confidence: 99%
“…Water-Alternating Gas (WAG) Injection. WAG is the most commonly used method for CO 2 enhanced oil recovery (Christensen et al 2001;Rogers and Grigg 2001). It is a challenge to simulate WAG when both gas dissolution and water vaporization are considered because of the rapid disappearance and reappearance of the hydrocarbon and aqueous phases.…”
Section: Proceed To Next Time-stepmentioning
confidence: 99%
“…Solvent injectivity is generally observed to decrease in field projects even though CO 2 has a lower viscosity than the fluids it is displacing (Henry et al 1981;Winzinger et al 1991). Rogers and Grigg (2001) stated that one possible reason for observed injectivity decreases is the impact of mineral reactions between brine and carbonates. At the Wasson Denver Unit, pre-and post-pilot core studies showed anhydrite dissolution during the water-injection portion of the WAG cycles, although the amount of dissolution was not significant (Mathis and Sears 1984).…”
mentioning
confidence: 99%